A rela????o da maturidade em gest??o de portf??lio de projetos e o alinhamento estrat??gico de tecnologia da informa????o nas organiza????es - Moraes, Heverton Roberto de Oliveira Cesar de (2015)
The project portfolio is a powerful tool for achieving the corporate strategies success. In a growing digital market, information technology projects has become important due toits contribution on new services and products maintaining and creation that will ensure organizations sustainable competitiveness. In this context the companies has been investing in portfolio management capabilitiesdevelopment, thus increasing their maturity and therefore success rates in their initiatives. Among the main goals of portfolio management is projects strategic alignment guarantee with organizational strategy, given this premise this study aimed to identify the existence and strength of the relationship between maturity in project portfolio management and Information Technology strategic alignment in organizations from various sectors of the economy. To achieve this objective it was studied the portfolio management processes, maturity in project portfolio management and IT strategic alignment, enabling the constructs formulation necessary for the electronic survey design. The research aimed to validate the relationship between project portfoliomanagementmaturity and IT strategic alignment within organizations using P3M3 and Luftman model. In addition we sought to investigate the influence of components: organizations sector and size, PMO existence and IT positioning in the relationship between project portfolio management maturity and IT strategic alignment. It was send electronic questionnaire to more than fifteen thousand members of the S??o Paulo PMI chapter and several information technology professionals in professional social networks. The data collected, from 121 responses, were treated, filtered and tabulated for quality analyzes using descriptive statistics, Spearman correlation analysis and correspondence analysis, besides the use of quantitative analysis with the use of structural equation modeling (SEM) using the Partial Least Squares technique, also known as Partial Least Squares (PLS). The results confirmed and existence and positive strength of the relationship between maturity in project portfolio management and IT strategic alignment, where 62.5% of IT strategic alignment can be explained byproject portfolio management maturity in GPP and IT positioningvariables. It was also possible to confirm the moderating influence of IT positioning in the relationship between project portfolio management maturity and strategic IT alignment. Although it was not foreseen in the original formulation of hypotheses, It was possible to identified the correlation between time of experience in project portfolio management with project portfolio management maturity and strategic alignmentvariable also, although medium impact. As an additional practice contribution it was proposed an: Integrated Maturity and IT Strategic AlignmentAnalysis Model, which provides a graphic representation of the values obtained fromproject portfolio management maturity andIT strategic alignment questionnaire in a general way or form the seven levels of maturity and six dimensions degrees strategic alignment perspective, allowing the diagnostics and action plans for IT and business executives.